2010
DOI: 10.1038/eye.2009.325
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of the late complications of proliferative diabetic retinopathy

Abstract: The late complications of proliferative diabetic retinopathy (PDR) comprise vitreous haemorrhage, tractional retinal detachment, combined tractional-rhegmatogenous retinal detachment, and severe fibrovascular proliferation (including macular distortion or dragging, tractional macular oedema, and media opacity due to fibrovascular tissue). This article will review the indications, techniques, and outcomes of vitrectomy surgery to treat these conditions. A careful assessment of the surgical anatomy, with particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 74 publications
(101 reference statements)
3
78
0
Order By: Relevance
“…The surgical plane was less clearly defined in these cases and the surgical procedures were categorized as major complexity procedures. 2 All patients had retinal breaks before or at the time of surgery (TRD/RRD). The case group consisted of eyes that underwent surgery from January 2013 to January 2014.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The surgical plane was less clearly defined in these cases and the surgical procedures were categorized as major complexity procedures. 2 All patients had retinal breaks before or at the time of surgery (TRD/RRD). The case group consisted of eyes that underwent surgery from January 2013 to January 2014.…”
Section: Methodsmentioning
confidence: 99%
“…2 Although a growing number of eyes with TMD and TRD/RRD are successfully treated with a single procedure, retinal re-detachment associated with fibrovascular proliferation or proliferative vitreoretinopathy (PVR) is still a major cause of failure of the surgery. 2,3 Previous studies have shown increased expression of inflammatory cytokines and growth factors in both PDR and PVR. [4][5][6] Considering the major role of inflammatory mediators, it is rational to consider anti-inflammatory medications as a potential modality for prevention of proliferation of post-vitrectomy membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of recurrent VH in PDR was reported in 13-54% of cases [4][5][6][7]; in our study this incidence was 11%.…”
Section: Discussionmentioning
confidence: 63%
“…The combination of high cutting speeds and small gauge instruments allows successful surgery in severe complications of PDR. PPV gives the possibility of removal of the fibrovascular tissue and blood from the vitreous cavity [5,6]. However, there is a risk of surgically induced complications, such as bleeding and VH, iatrogenic retinal breaks, recurrent RD, and glaucoma.…”
Section: Introductionmentioning
confidence: 99%